Socialization Of The 2017-2020 Indoor Volley Ball Regulations On Volley Ball Sports Boarders In Pamona Utara District Poso District - Didik Purwanto; Tri Murtono; Christian Kungku; Nyoman Sukrawan; Arief Aditya Rifandy (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Volleyball is a sport that is quite popular in Indonesia, especially in the province of Central Sulawesi. In the volleyball game, a player is not only required to master the basic techniques in volleyball, but players are also required to master the official rules of volleyball. And the coach or coach is also required to master the rules of the volleyball game and must know the task when bringing the team to compete. North Pamona District is one of the sub-districts in Poso Regency. Volleyball championships in North Pamona District always routinely carry out volleyball tournaments, but the coaches or coaches who bring the team do not really understand their duties in the field and are not supported by knowledge of the latest volleyball game rules. This situation requires the holding of socialization of the rules of indoor volleyball 2017-2020 in North Pamona District. The socialization of the 2017-2020 indoor volleyball rules will be held on August 13, 2021 at Sulewana Village, North Pamona District, from 07.00-17.00 WITA, the socialization material refers to the rules of indoor volleyball 2017-2020. Implementation of socialization for 1 day, which includes theory and practice. Participants came from volleyball coaches in every village in North Pamona District. There were 15 participants in the socialization activity.